2016
DOI: 10.1002/jssc.201600585
|View full text |Cite
|
Sign up to set email alerts
|

Ion chromatography with the indirect ultraviolet detection of alkali metal ions and ammonium using imidazolium ionic liquid as ultraviolet absorption reagent and eluent

Abstract: Indirect ultraviolet detection was conducted in ultraviolet-absorption-agent-added mobile phase to complete the detection of the absence of ultraviolet absorption functional group in analytes. Compared with precolumn derivatization or postcolumn derivatization, this method can be widely used, has the advantages of simple operation and good linear relationship. Chromatographic separation of Li(+) , Na(+) , K(+) , and NH4 (+) was performed on a carboxylic acid base cation exchange column using imidazolium ionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…In IUV detection, the selection of the UV absorption reagent is very important. Nicotinamide and 4‐aminophenol hydrochloride are the common UV absorption reagents , and pyridinium and imidazolium ILs with strong UV absorption can also be used as the UV absorption reagents . The effects of niacinamide, 4‐aminophenol hydrochloride, and two ILs ([EMIm][BF 4 ] and [EPy][BF 4 ]) as the UV absorption reagents on the determination of Fe 2+ and Fe 3+ were investigated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In IUV detection, the selection of the UV absorption reagent is very important. Nicotinamide and 4‐aminophenol hydrochloride are the common UV absorption reagents , and pyridinium and imidazolium ILs with strong UV absorption can also be used as the UV absorption reagents . The effects of niacinamide, 4‐aminophenol hydrochloride, and two ILs ([EMIm][BF 4 ] and [EPy][BF 4 ]) as the UV absorption reagents on the determination of Fe 2+ and Fe 3+ were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…In IUV detection, the selection of the UV absorption reagent is very important. Nicotinamide and 4-aminophenol hydrochloride are the common UV absorption reagents [42], and pyridinium and imidazolium ILs with strong UV absorption can also be used as the UV absorption reagents [16][17][18][19][20][21][22] 4 ] were used as the UV absorption reagent, respectively, the two iron ions could be completely separated with a good peak shape. When 4-aminophenol hydrochloride and nicotinamide were used as the UV absorption reagent, respectively, the two iron ions could not be separated, and the baseline noise value was large when nicotinamide was used as the UV absorption reagent.…”
Section: Effect Of Different Uv Absorption Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their unique properties, their use has attracted considerable interest, including an increasing number of publications on their use in preparing stationary phases of HPLC . An active research is found in many reports on the role of ILs to modify the retention of different types of solutes in LC . Based on their UV absorption, imidazolium ILs have been applied as background reagents for determination of IL cations in the HPLC and IC with UV indirect detection.…”
Section: Introductionmentioning
confidence: 99%